Monitoring Perubahan Garis Pantai Menggunakan Citra Satelit Sentinel-2 di Kelurahan Manggar Kota Balikpapan Tahun 2016 – Tahun 2024 - Yansi, Muhammad Adry; Kurniadin, Nia; Suryalfihra, Shabri Indra; Wumu, Romansah (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2025)
The coastal area has dynamic characteristics that continuously change due to the influence of complex interactions between natural factors and human activities. These changes are triggered by pressures from natural phenomena (such as erosion and flooding) as well as human activities on land and at sea, such as the development of settlements and the conversion of forests into agricultural land or aquaculture. The impacts of these activities can disrupt the stability of coastal ecosystems. In the coastal area of Manggar Village, which is home to several tourist destinations, the presence of tourist attractions and the development of supporting tourism infrastructure have the potential to alter the structure of the coastline. This activity necessitates research to conduct periodic monitoring in the form of determining the coastline affected by the extent of erosion and accretion from 2016 to 2024 every two years. The objective of this research is to present biannual data related to the dynamics of coastline changes and to measure the area affected by erosion (degradation) and accretion (sedimentation addition) in the coastal area of Manggar Village during the period of 2016-2024. The method used leverages remote sensing technology through Sentinel-2 image analysis with the NDWI (Normalized Difference Water Index) algorithm and land-sea segmentation techniques to accurately separate water and land areas. The results of this research are expected to serve as a scientific reference for sustainable coastal area management. This study shows results indicating that the coastline length in 2016 was 6,222 m or 6.2 km, and in 2024 it was 6,130 m or 6.1 km. The erosion from 2016 to 2024 covered an area of 115,770 m², while the accretion covered an area of 14,600 m². The findings of this research provide a clear picture